Zero Tolerance of Children’s Sexual Abuse from Interreligious Dialogue - Cristina M. Pulido; Ana Vidu; Roseli Rodrigues de Mello; Esther Oliver (Religions, 2021)
Child sexual abuse is a social problem that concerns our societies. The sustainable development goals have highlighted the eradication of child sexual abuse as one of the highest-priority goals of this century. Breaking the silence within religious communities is an essential step going forward. Therefore, establishing a dialogue between people of different religions is crucial to achieving this goal. The purpose of this article is to explore whether there are current interreligious dialogue initiatives based on scientific recommendations to prevent child sexual abuse. The method used herein is a qualitative document analysis of the selected initiatives. The results indicate that interreligious dialogue initiatives include scientific recommendations in their prevention programs. Furthermore, these successful initiatives connect religious values and the need to support victims and to break their silence. Based on these results, it can be concluded that interreligious initiatives for child sexual abuse prevention programs based on scientific evidence are crucial in order to eradicate child sexual abuse.